Multifunctional Thrombin-Activatable Polymer Capsules for Specific Targeting to Activated Platelets - Gunawan, Sylvia T (Advanced materials (Deerfield Beach, Fla.), 2015)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.